Patterns of Relationship between Islamic Values and Social Science Issues in Thematic Books for Grade IV Elementary School - Rahmi, Rina (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The purpose of this research is to study and analyze the regularity of the relationship between Islamic values and social science subjects/materials contained in the thematic book theme 3